Molecular phylogenetics of the Onobrychis genus (Fabaceae: Papilionoideae) using ITS and trnL–trnF DNA sequence data - Safaei Chaei Kar, S; Ghanavati, F; Naghavi, M. R; Amirabadi-zade, H; Rabiee, R (Australian journal of botany, 2014)
Onobrychis, comprising more than 130 species, is a genus of the family Fabaceae. At this time, the interspecies relationship of this biologically important genus is still a subject of great discussion and debate. To help resolve this disagreement, we used molecular phylogeny to analyse internal transcribed spacer (ITS) and trnL–trnF sequences of 76 species of Onobrychis. Bayesian interference, maximum parsimony and maximum likelihood analyses of nuclear ITS and plastid trnL–trnF DNA sequence data generated trees with strong posterior probability for two groups: Onobrychis subgen. Sisyrosema (including: Heliobrychis, Hymenobrychis, Afghanicae and Anthyllium sections) along with Laxiflorae section in Group I and Onobrychis subgen. Onobrychis (except Laxiflorae section) in the other (Group II). The Laxiflorae section roots back to the ancestral node for Sisyrosema subgen. O. viciifolia (cultivated species), which is closely associated with O. cyri var. cyri, suggesting that the latter may be a wild progenitor of O. viciifolia. The present study supported the paraphyly of subgenera Onobrychis and Sisyrosema. The study proposed the paraphyletic nature of the sections Onobrychis, Dendrobrychis, Heliobrychis and Hymenobrychis. Together with our molecular phylogenetic analyses we present a review of Onobrychis morphology and discuss and compare our results with those of earlier morphological and molecular phylogenetic analyses.